Odpowiedzi

  • Użytkownik Zadane
2010-01-28T17:52:37+01:00
-(x-4)² -(x+4)(x-4)=0
-x²+8x-16-x²+16
8x=16
x=0

(x-3)(x+3)-(2x-1)²=x(6-3x)-9
x²-9-4x²+4x-1=6x-3x²-9
-10+4x=6x-9
-2x=1
x=-½

-2+(x+2)²=2x ²- (x+1)²
-2+x²+4x+4=2x²-x²-2x-1
2+4x=-2x-1
2+6x=-1
6x=-3
x=-½
Najlepsza Odpowiedź!
2010-01-28T17:56:19+01:00
(x-4)²-(x+4)(x-4)=0
x²-8x+16-(x²-16)=0
x²-8x+16 -x² +16 = 0
-8x=32 /:(-8)
x=-4

(x-3)(x+3)-(2x-1)²=x(6-3x)-9
(x²-9)-(4x²-4x+1)=6x-3x²-9
x²+9-4x²+4x-1=6x-3x²-9
x²-4x²+4x-6x+3x²=1-9-9
-2x=-17 /:(-2)
x=8,5

2+(x+2)² =2x ² - (x+1)²
2+x²+4x+4=2x² -(x²+2x+1)
2+x²+4x+4=2x² -x²-2x-1
x²+4x-2x²+x²+2x=-2-4-1
6x=-7 /:6
x = - 1 1/6

koniec..;D